1979
DOI: 10.1042/bj1770319
|View full text |Cite
|
Sign up to set email alerts
|

The multiple forms and kinetic properties of the N-acetyl-β-d-hexosaminidases from colonic tumours and mucosa of rats treated with 1,2-dimethylhydrazine

Abstract: The separation and purification of the N-acetyl-beta-D-hexosaminidase activities from tumours induced by 1,2-dimethylhydrazine in the rat colon and from colonic mucosa of tumour-bearing animals are reported. Mucosa contained N-acetylhexosaminidases A and B, as well as a third form whose properties with regard to electrophoretic mobility and thermostability lay between those of A and B. Tumours contained only N-acetylhexosaminidase A and B activities. Each form possessed both N-acetylglucosaminidase (EC 3.2.1.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The specific activity determined was 3.58 ,u mol / hr / mg of protein. The value was much higher than that (0.0111umol/hr/mg of protein) of rat colonic mucosa of a different strain reported by Mian et al (1979), but was comparable with that (1.95 ,u mol/hr/mg of protein) of human colonic mucosa (Tsao et al 1979). These data suggested that the enzyme solubilization was achieved to an extent which is comparable with or much higher than that reported previously.…”
Section: The Specific Activity Of Glycosidasesmentioning
confidence: 59%
See 4 more Smart Citations
“…The specific activity determined was 3.58 ,u mol / hr / mg of protein. The value was much higher than that (0.0111umol/hr/mg of protein) of rat colonic mucosa of a different strain reported by Mian et al (1979), but was comparable with that (1.95 ,u mol/hr/mg of protein) of human colonic mucosa (Tsao et al 1979). These data suggested that the enzyme solubilization was achieved to an extent which is comparable with or much higher than that reported previously.…”
Section: The Specific Activity Of Glycosidasesmentioning
confidence: 59%
“…On the other hand, no significant differences in this proportion were shown in rat colonic adenocarcinoma and human prostatic carcinoma (Mian et al 1979;Whitehurst et al 1982). In the present study, two components of /3-N-acetylglucosaminidase corresponding chromatographically to the A and B isozymes were termed the A and B forms, respectively, according to the designation by Mian et al (1979).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations